ORGANIZATIONAL JUSTICE AND THE RELATIONSHIP BETWEEN OF SECONDARY TRAUMATIC STRESS AND BURNOUT IN HOSPITAL EMPLOYEES (Third Sector Social Economic Review, 2024)
In this study, the concepts of organizational justice, secondary trauma stress and burnout are explained and discussed specifically for healthcare professionals. The aim of the study is to investigate the relationship between organizational justice perception and secondary traumatic stress and burnout in hospital employees, and the relationship between these variables and demographic factors. Data set of the research; It includes 268 surveys collected from active employees in a private hospital operating in Ankara. Data entry and analysis were made with the SPSS program. Frequency distribution, Cronbach's alpha, Pearson moment correlation, t-test, one-way analysis of variance, post-hoc test after lds, multiple analysis of variance and simple linear regression analysis methods were used in the analysis of the data. As a result of the research, there is a negative significant relationship between perception of organizational justice and burnout; A strong positive relationship was also found between secondary traumatic stress and burnout. It was found that burnout levels vary significantly according to occupational groups and professional experience periods.
Keywords: Organizational Justice; Burnout; Secondary Traumatic Stress; Hospital Employees